Hubungan Antara Kecerdasan Emosional Dan Efikasi Komunikasi Pada Pemimpin Organisasi : Studi Kasus Pada Perusahaan Manufactur Dikota Bandung - Almadina Rakhmaniar (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2023)
This study aims to analyze the influence of emotional intelligence and communication efficacy on leadership effectiveness in organizational leaders in manufacturing companies in Bandung City. The results of multiple regression analysis show that emotional intelligence (B = 0.568, p < 0.001) and communication efficacy (B = 0.482, p < 0.001) both have a positive and significant influence on leadership effectiveness. The resulting regression model has a coefficient of determination (R²) of 0.672, indicating that 67.2% of the variability in leadership effectiveness can be explained by emotional intelligence and communication efficacy. This finding indicates that increasing emotional intelligence and communication efficacy can increase leadership effectiveness. Therefore, the development of emotional intelligence and communication efficacy is very important in an effort to improve leadership effectiveness in organizations.